Efficacy of Trans-nasal Endoscopic Sphenopalatine Artery Ligation in the Management of Recurrent Posterior Epistaxis (KYAMC Journal, 2021)
Background: Recurrent posterior epistaxis is a challenging problem for most otolaryngologists. Of the several proposed treatment modalities, endoscopic ligation of SPA (Sphenopalatine artery) provides a simple and effective solution with relatively minor complications.Objectives: Aim of this study was to find out the success rate and complications of endoscopic ligation of SPA in the management of recurrent posterior epistaxis.Materials and Methods: This was an observational study conducted from Jan 2019 to Jan 2021. Total 60 patients were included in this study. Inclusion criteria were - recurrent epistaxis (at least 4 episodes in last 2 months) with bleeding point not seen in anterior rhinoscopy, Failure of previous conservative management with medications and nasal packing, age between 18–60 years of both sexes. All the patients underwent trans-nasal endoscopic Sphenopalatine artery ligation, and patients were followed up for 12 weeks to identify repeated bleeding and to evaluate complications.Results: In this study male to female ratio was 1.5:1. Mean age of study group was 44.66 (±8.62) years. No recurrent bleeding occurred in 51 (85%) and in 9 (15%) nasal bleeding occurred in the 2 months postoperative period. Anesthesia of incisor teeth occurred in 18 patients (30%), 22 patients (37%) complained about increased nasal crusting.Conclusion: Endoscopic ligation of Sphenopalatine artery shows good outcome in prevention of further episodes of epistaxis in most patients. Although some minor complications can occur, these are manageable.KYAMC Journal. 2021;12(3): 133-137